Magnetic resonance imaging fails to show evidence of reduced endolymphatic hydrops in gentamicin treatment of Ménière's disease - Fiorino, Francesco; Pizzini, Francesca B; Barbieri, Franco; Beltramello, Alberto (Otology & neurotology, 2012)
To verify the hypothesis that intratympanic (IT) gentamicin (Gent) treatment in Ménière's disease (MD) is capable of reducing endolymphatic hydrops (EH), as evaluated by 3-dimensional fluid-attenuated inversion recovery (3D-FLAIR) sequence in a 3-Tesla magnetic resonance imaging (MRI) unit, after IT gadolinium administration. A total of 8 patients (5 men and 3 women; aged 40-78 yr; median, 60 yr) with definite MD participated in the investigation. The duration of the disease ranged from 1 to 10 years (median, 4 yr), with a prevalence of vertigo spells of 1 to 6 per month (median, 3.1), as calculated in the last 6 months. A 3D-FLAIR MRI was performed 24 hours after IT injection of diluted gadobutrol. Intratympanic Gent injection was performed in a period variable from 1 to 3 weeks after 3D-FLAIR MRI. A single-shot administration protocol was attempted with additional injections administered on demand in the case of relapsing vertigo spells. MRI was repeated after 3 to 12 months (median, 8 mo) after treatment. The degree and extension of EH as evaluated by 3D-FLAIR MRI was compared from images obtained pre- and post-ITGent administration. After ITGent administration, 4 patients did not show any MRI modification, 3 patients showed a worsening of EH in one site, and 1 patient showed a worsening in two sites. No subjects presented reduction of EH. No evidence of reduced EH following ITGent treatment has been shown in the present imaging investigation.